Prognostic Factors of Recurrent Cervical Cancer Stage IA2–IIA2: A Post-Surgical Treatment Analysis - Argy, Gabriella; Nuryanto, Kartiwa Hadi; Hellyanti, Tantri (Indonesian Journal of Cancer, 2024)
Background: Cervical cancer is the most common female reproductive organ malignancy. Despite the prompt diagnosis and proper management based on the disease’s stage, the recurrent rate remains high, ranging from 18 to 44.3%. Prognostic factor detection may be the first step in reducing recurrent disease. To our knowledge, there are no studies that report the recurrence rate of cervical cancer and the prognostic factors in Indonesia yet. This study aims to report the recurrent rate of cervical cancer stage IA2–IIA2 and the prognostic factors.Methods: This is a retrospective cohort study. Histopathology results from 382 cervical cancer stage IA2–IIA2 patients who underwent radical hysterectomy and pelvic lymphadenectomy were reviewed. Bivariate analysis was performed to compare recurrent disease based on 7 prognostic factors: lymph node status, tumor size, depth of stromal invasion, lymphovascular space invasion (LVSI), parametrial involvement, histology type, and vaginal resection margin status.Results: Most cervical cancer patients with stage IA2–IIA2 were more than 40 years old, with a mean age was 52 years. The recurrent rate was 12%. Prognostic factors that were significantly associated with recurrence were tumor size ≥ 4 cm; RR 2.242 (95% CI 1.161–4.332) and LVSI; RR 2.037 (95% CI 1.039–3.994).Conclusions: The recurrence rate of cervical cancer stage IA2–IIA2 in Dr. Cipto Mangunkusumo National Hospital was 12%. Prognostic factors that were significantly associated with recurrence were tumor size ≥ 4 cm and LVSI.